2023
DOI: 10.1021/acsami.2c21013
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Silk Nanostructured Films with Antifungal and Antibacterial Activity

Abstract: The rapid emergence of drug-resistant bacteria and fungi poses a threat for healthcare worldwide. The development of novel effective small molecule therapeutic strategies in this space has remained challenging. Therefore, one orthogonal approach is to explore biomaterials with physical modes of action that have the potential to generate antimicrobial activity and, in some cases, even prevent antimicrobial resistance. Here, to this effect, we describe an approach for forming silk-based films that contain embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…We were able to control nanoparticle size by varying the sodium selenite concentration, with sizes ranging from roughly 60 to 140 nm. 41 The ability to finetune nanoparticle size is of critical importance in biological applications as it can impact cellular interactions and the corresponding pharmacokinetics. 42,43 The SeNPs were found to have uniform shapes and morphologies that make them easy to integrate into materials for delivery applications (ESI, † Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to control nanoparticle size by varying the sodium selenite concentration, with sizes ranging from roughly 60 to 140 nm. 41 The ability to finetune nanoparticle size is of critical importance in biological applications as it can impact cellular interactions and the corresponding pharmacokinetics. 42,43 The SeNPs were found to have uniform shapes and morphologies that make them easy to integrate into materials for delivery applications (ESI, † Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we chose to use vitamin C to reduce Na 2 SeO 3 , and BSA as a capping and stabilizing agent, to produce SeNPs for three main reasons. Firstly, it is a simple, fast, and productive method without the need for specific equipment [ 4 , 6 , 30 , 43 ]. Secondly, the size of the SeNPs can be controlled by adjusting the molar ratio of the two reactants, vitamin C and Na 2 SeO 3 , and the speed at which the reaction is stirred [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…SeNPs have been shown to exhibit antibacterial activity against a wide range of microorganisms, including bacteria, viruses, and fungi [ 2 , 4 , 8 , 10 , 27 , 28 , 43 , 46 ]; however, our study is the first one that examined the antibacterial effect of SeNPs synthesized by vitamin C reduction of Na 2 SeO 3 against as many as 10 common food-borne bacteria, and also utilized SEM to help elucidate the possible mechanisms of the antibacterial action of SeNPs. Among the 10 test bacteria selected for the present study, the SeNPs showed the strongest effect against Listeria monocytogens (ATCC15313), with a 50% inhibition at 1 µg /mL, which reached ~80% inhibition at 10 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs are known to have strong antimicrobial and antifungal properties, and studies have shown that they can disrupt cellular processes and metabolic pathways in a wide range of microorganisms and fungi (Anees Ahmad et al 2020 ; Bruna et al 2021 ; de Lacerda Coriolano et al 2021 ; Nadhe et al 2019 ). Similarly, SeNPs have been shown to have antifungal and antiviral effects, suggesting that they, too, may interfere with essential cellular processes (Ferro et al 2021 ; Sharmin et al 2021 ; Toprakcioglu et al 2023 ). In addition, both AgNPs and SeNPs have been shown to induce oxidative stress and increase the production of reactive oxygen species, which can trigger cell death pathways (Afifi and Oshiba 2018 ; Ferro et al 2021 ; Gad et al 2021 ; KD and Venugopal 2022 ; Lin et al 2021 ; Martínez-Esquivias et al 2021 ; Rashidi et al 2022 ; Vahdati and Tohidi Moghadam 2020 ).…”
Section: Discussionmentioning
confidence: 99%